2022
DOI: 10.1155/2022/8345736
|View full text |Cite
|
Sign up to set email alerts
|

Full Endoscopic Surgery for Thoracic Pathology: Next Step after Mastering Lumbar and Cervical Endoscopic Spine Surgery?

Abstract: Thoracic disc herniation and stenosis are relatively rare, and various symptoms make them difficult to diagnose. Due to the complexity of neural and vascular structure, surgical treatment of thoracic pathology is challenging. Endoscopic spine surgery is an emerging minimally invasive surgical option. Based on wide experience on the cervical and lumbar spine, an endoscopic approach for the thoracic pathology can be performed beyond the learning curve. Transforaminal approach for thoracic disc herniation, endosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The excellent as well as good outcomes and the advantages of full-endoscopic spine surgery have been proven for the treatment of herniated discs and stenoses in the lumbar and cervical vertebrae (11,17,18). Additionally, the next step after mastering lumbar and cervical endoscopic spinal surgery is managing the thoracic pathology with the full-endoscopic technique (19). Recently, many surgeons worldwide tried various minimally invasive surgery techniques, such as surgery-transforaminal lumbar interbody fusion, video-assisted thoracoscopic surgery, microendoscopic surgery, and full-endoscopic surgery, to treat thoracic pathology (4,9,(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…The excellent as well as good outcomes and the advantages of full-endoscopic spine surgery have been proven for the treatment of herniated discs and stenoses in the lumbar and cervical vertebrae (11,17,18). Additionally, the next step after mastering lumbar and cervical endoscopic spinal surgery is managing the thoracic pathology with the full-endoscopic technique (19). Recently, many surgeons worldwide tried various minimally invasive surgery techniques, such as surgery-transforaminal lumbar interbody fusion, video-assisted thoracoscopic surgery, microendoscopic surgery, and full-endoscopic surgery, to treat thoracic pathology (4,9,(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…After reaching the plateau of the learning curve, the full-endoscopic technique can be performed with a surgical time comparable to that of other techniques but with less bleeding, a shorter hospital stay, less postoperative pain, and a shorter rehabilitation time [1,2,6]. After several years, some authors [37][38][39] demonstrated the effectiveness of the technique on the thoracic spine, with an improvement in pain intensity and neurological deficit in patients with hypertrophy or calcification of the ligamentum flavum. The presence of the spinal cord may at first glance cause concern among spine surgeons, but the full-endoscopic technique may be a good option in the treatment of posterior central compression in the thoracic spine, with few reported complications [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, patients with LSS have a variety of conservative options including pain medications and physical therapy. Surgical intervention for LSS is common in cases when patients begin to see neurological deterioration and symptoms [ 115 , 116 ]. The standard of care has been decompression surgery, requiring significant manipulation of spinal muscles [ 116 ].…”
Section: Emerging Treatment Optionsmentioning
confidence: 99%
“…Surgical intervention for LSS is common in cases when patients begin to see neurological deterioration and symptoms [ 115 , 116 ]. The standard of care has been decompression surgery, requiring significant manipulation of spinal muscles [ 116 ]. This approach has been seen to increase the risk of postoperative complications [ 117 ].…”
Section: Emerging Treatment Optionsmentioning
confidence: 99%